ENERGÍA HÍBRIDA PARA ÁREAS RURALES DISPERSAS DE LA PROVINCIA DE SANTIAGO DEL ESTERO (ARGENTINA) EN EL MARCO DE LOS ODS 2030 Y LAS MDBA - Franco Fernández; Alejandro Ferreiro; Carlos Juárez; Carlos Cadena; Luis Moyano (Revista Ingeniería, Matemáticas y Ciencias de la Información)
The provision of sustainable energy solutions in Rural Areas with Dispersed Population (ARPoDs) without the possibilityof interconnection to power grids in the Province of Santiago del Estero (Argentina), motivates a preliminary analysis ofthe context at the global, national and provincial levels, and then to explore options that integrate different energysources applied to a case study, specifically to the community located in the town of Las Viboritas, in the Mitre departmentof the aforesaid province. The purpose of the work is to present the analysis of the energy situation and possible energysupply solutions in the field of ARPDs from an integrative perspective, based on the 2030 ODS and the so-called New Rurality. In addition, the study of an alternative using solar-wind hybrid energy systems isdescribed, contrasted with other options, even based on fossil fuels. A recognized computational tool is applied thatallows optimizing the operation of systems with hybrid energy sources for each hour of the year. The design is carried outfrom the quantification of the demand, the dimensioning and cost of the technologies that make up the hybrid system, andthe availability of renewable resources at the site under study. As a result, a solar-fossil hybrid system with a lithiumaccumulation bank is proposed, since this system presents greater reliability and safety for its operation as an isolatednetwork.